Engineering Dual Single‐Atom Sites on 2D Ultrathin N‐doped Carbon Nanosheets Attaining Ultra‐Low‐Temperature Zinc‐Air Battery - Cui, Tingting; Wang, Yun‐Peng; Ye, Tong; Wu, Jiao; Chen, Zhiqiang; Li, Jiong; Lei, Yongpeng; Wang, Dingsheng; Li, Yadong (Angewandte Chemie International Edition, 2022)
Herein, a novel dual single‐atom catalyst comprising adjacent Fe‐N4 and Mn‐N4 sites on 2D ultrathin N‐doped carbon nanosheets with porous structure (FeMn‐DSAC) was constructed as the cathode for a flexible low‐temperature Zn‐air battery (ZAB). FeMn‐DSAC exhibits remarkable bifunctional activities for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Control experiments and density functional theory calculations reveal that the catalytic activity arises from the cooperative effect of the Fe/Mn dual‐sites aiding *OOH dissociation as well as the porous 2D nanosheet structure promoting active sits exposure and mass transfer during the reaction process. The excellent bifunctional activity of FeMn‐DSAC enables the ZAB to operate efficiently at ultra‐low temperature of −40 °C, delivering 30 mW cm−2 peak power density and retaining up to 86 % specific capacity from the room temperature counterpart. A Fe/Mn dual single‐atom catalyst with an excellent bifunctional activity is prepared as the cathode for a flexible low‐temperature Zn‐air battery (ZAB). Profiting from the combined Fe/Mn dual‐site effect as well as the porous 2D nanosheet structure, the ZAB could operate efficiently at the ultra‐low temperature of −40 °C.